TEACHER, STUDENT, AND PARENT VIEWS ON ELEMENTARY SCHOOL MATHEMATICS LESSON DURING DISTANCE EDUCATION PROCESS - Gökçe, Yavuz; Çetin, Barış (International Online Journal of Education and Teaching, 2024)
This study investigated the perspectives of primary school teachers, students, and parents on fourth-grade mathematics distance education during the 2020-2021 academic year. Using a qualitative research approach with a case study design, the research included 11 fourth-grade teachers, 12 students, and 12 parents from official primary schools in Çerkezköy, Tekirdağ province, Turkey during the spring semester of the 2021-2022 academic year. Criterion sampling principles were followed for participant selection. Data collection involved semi-structured interviews, and content analysis was employed for analysis. According to the findings of the study, the classroom teachers highlighted the benefits of distance education, such as increased parental support, uninterrupted learning, and self-directed student learning, whereas the challenges included supervision difficulties, assessment reliability, limited one-on-one teaching, and extended screen time. The students found positive aspects in the seamless continuation of learning during distance education but faced challenges such as short lesson durations, technical issues, and inadequate teaching materials. The parents noted positive effects on their children’s mathematics learning, including educational continuity and independent learning, whereas the challenges included the lack of one-on-one teaching, reliance on technology, and adaptation issues.